W2, 2 A Priori Bounds for a Class of Elliptic Operators. (11th October 2011) - Monsurrò, Sara; Salvato, Maria; Transirico, Maria
Abstract : We obtain someW 2, 2 a priori bounds for a class of uniformly elliptic second-order differential operators, both in a no-weighted and in a weighted case. We deduce a uniqueness and existence theorem for the related Dirichlet problem in some weighted Sobolev spaces on unbounded domains.